The Evaluation UPK Performance Managing PNPM Revolving Fund In Banyudono (2015-2017) - Dipa Nuswantara (University of Darussalam Gontor, 2017)
The revolving fund of community-based awareness programs aims to provide capital access for the poor that is expected to stimulate economic activity. The districs of Banyudono has 15 sub-districts which recivied this funding program. There are 4 ratios to assest UPK’s performance in managing revolving loan funds they are LAR, PAR, CCr, and ROI. In the LAR ratio showing loan arrears more than three months the average assessment during 2015 to 2017 has a value of 66.5% which means suspend. PAR ratio shows the number of KSM members who are at risk of having arrears more than three months has an average value of 52.2% which means suspend. The CCr ratio showing the ability of UPK to finance its operational activities with its revenue has an average value from 2015 to 2017 about 289.9% which means that it is adequate. The ROI ratio shows the ability of UPK to generate profit from their revolving loans has an average value of -10.1% means delayed. In general, the performance of UPK in Banyudono sub-district still has not met expectations.